The Relationship between Blood Groups and Dermatophytoses of Women in Karbala City - Aseel Najah Sabour (Journal of Global Pharma Technology, 2018)
Objective: The current study aims to investigate the relationship between dermatophytoses and blood groups in women. Methods: Thirty women patients with dermatophytoses who visited the hospitals in the holy province of Karbala were diagnosed with the clinical manifestations of them by dermatologists specialists in these hospitals, and blood samples were obtained in the laboratory and the ABO examination for them to know their blood groups and Rh. Results: Patients are women aged 3 to 90 years. The age group 33-47 years is the highest among the patients, reaching 30%. Most patients (96.67%) were Rh+, while 3.33% were Rh-. People with blood group A are the most likely to develop dermatophytoses with percentage 36.67% of patients, followed by women patients of blood group B with 26.67% , women patients of blood group O were 20%, while AB blood group women patients were the lowest with 16.66%.The clinical manifestations tinea capitis of dermatophytoses were the most common among the others , and tinea capitis significantly correlated with blood group A, and the rest of the clinical manifestations showed no significant correlation with any of the blood groups. Conclusion: There is a relationship between infection of dermatophytoses and blood groups, specifically between tinea capitis with blood group A. Keywords: Dermatophytosis; Blood groups; Tinea capitis.